2000
DOI: 10.1038/35039544
|View full text |Cite
|
Sign up to set email alerts
|

Steps and fluctuations of Listeria monocytogenes during actin-based motility

Abstract: The actin-based motility of the bacterium, Listeria monocytogenes, is a model system for understanding motile cell functions involving actin polymerization. Although the biochemical and genetic aspects of Listeria motility have been intensely studied, biophysical data are sparse. Here we have used high-resolution laser tracking to follow the trailing ends of Listeria moving in the lamellae of COS7 cells. We found that pauses during motility occur frequently and that episodes of step-like motion often show paus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
101
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(115 citation statements)
references
References 27 publications
14
101
0
Order By: Relevance
“…The first assumption, that the energetic state of the bacterium is well approximated by a two-state model, is satisfied if, as suggested by existing experimental data, the bacterium is strongly attached to the surrounding actin gel (18) and does not move except when the attachment is broken, e.g., moves in discrete steps or intervals (19,20). Under these conditions, at any moment in time the bacterium occupies one of two possible states, fixed and moving, with the energy difference between the states determined by the energy required to break the adhesion between the bacterium and surrounding actin gel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first assumption, that the energetic state of the bacterium is well approximated by a two-state model, is satisfied if, as suggested by existing experimental data, the bacterium is strongly attached to the surrounding actin gel (18) and does not move except when the attachment is broken, e.g., moves in discrete steps or intervals (19,20). Under these conditions, at any moment in time the bacterium occupies one of two possible states, fixed and moving, with the energy difference between the states determined by the energy required to break the adhesion between the bacterium and surrounding actin gel.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming that the system is near thermal equilibrium and also that the time scale of the measurement is long compared with the transition time between states, the time-average probability of occupying either state then depends exponentially on the time-average free energy difference between the states. According to high-bandwidth laser interferometry measurements of bacterial motion (19,20), the latter condition is true for the relatively long sample intervals that were used here (2 sec).…”
Section: Resultsmentioning
confidence: 99%
“…This work also tracked the movement of the chromosomes during spindle migration and found that the path of chromosomes movement is not straight, as suggested by a low displacement/path length ratio. In addition, it has been observed the movement of chromosomes exhibits a periodic pattern similar to the actin polymerization-based motility of Listeria mutants or beads coated with verprolin homology, cofilin homology, and acidic region (VCA) (subdomain of Wiskott-Aldrich syndrome protein (WASP), an Arp2/3 complex activator) [Kuo and McGrath, 2000;Bernheim-Groswasser et al, 2002]. Taking together, these observations led to an alternative model in which the actin filaments in chromosome vicinity could push the spindle toward the cortex.…”
Section: Spindle Migration: Where and How The Force Is Generatedmentioning
confidence: 92%
“…Kuo and McGrath (12) showed that the diffusion coefficient of L. monocytogenes undergoing intracellular motility is much smaller than expected for a freely diffusing object of the same size. Gerbal et al (13) used optical trapping to directly demonstrate the firm attachment of the actin tail to an ActA-coated plastic bead.…”
mentioning
confidence: 95%